Dosimetric comparison of dose accumulation between rigid registration and deformation registration in intensity-modulated radiation therapy for large volume non-small cell lung cancer - Ren, Jianxin; Gong, Guanzhong; Yao, Xinsen; Yin, Yong (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: To evaluate the cumulative dose to the target volumes and organs at risk (OARs) after replanning during intensity-modulated radiation therapy (IMRT) for large volume non-small cell lung cancer (NSCLC) based on rigid registration and deformation registration technologies. Methods: Thirty patients with large volume NSCLC who were treated with IMRT were selected, and two four-dimensional computed tomography (4DCT) scans were acquired before radiotherapy and after 20 fractions of radiotherapy. The initial treatment plan (Plan1) based on the average density projection CT (CT1-avg) of the first 4DCT images and the second treatment plan (Plan2) based on CT2-avg of the second 4DCT images were calculated. Then, the dose distributions of Plan2 and Plan1 were accumulated based on rigid and deformation registration technologies to obtain Planrig and Plandef, respectively. Finally, the volume changes of the gross tumor volume (GTV) and OARs between the two CT scans, and the dose-volume parameters among Plan1, Plan2, Planrig and Plandef were compared. Results: Compared with those on the first CT, the mean GTV and heart volume on the second CT decreased by 44.2% and 5.5%, respectively, while the mean volumes of the ipsilateral lung, contralateral lung and total lung increased by 5.2%, 6.2% and 5.8%, respectively. The differences in the above volume parameters between the two CT scans were statistically significant (P0.05), and those of Planrig and Plandef decreased slightly (P